Studi Komparatif Antara Justice Collaborator Dengan Whistleblower Dalam Tindak Pidana Korupsi - Laura Naomi Rotua Gultom (Faculty of Law, Universitas Lampung, 2020)
The Whistleblower and Justice Collaborator play a role in facilitating the disclosure of criminal acts of corruption, because none other than people involved in institutions suspected of corrupt practices and in other words the witness's information is key for disclosure of a case of corruption. The problem in this study is whether the similarities and differences between justice collaborator and whistleblowers in corruption, and how is the legal protection between justice collaborator and whistleblower in criminal acts of corruption. This research uses normative juridical and juridical empirical research methods with qualitative data analysis. The data sources used in this study are primary, secondary, and tertiary legal materials. The results showed that whistleblower equations and justice collaborator were in 3 (three) categories, namely vision and mission in uncovering criminal acts of corruption, guarantee of protection in the form of physical, psychological and legal protection, and awards where whistleblowers and justice collaborators cannot be prosecuted criminal and civil and given sentence relief. In addition to these equations, there are also differences between whistleblowers and justice collaborator divided into 4 (four) categories, namely subject, motivation, guarantee of protection, and procedural law. The protection between justice collaborator and whistleblower in corruption namely legal protection in the form of keeping the identity of the witness confidential and then provides security for witnesses in the trial process by providing physical, psychological, and legal protection.